(untitled) (Journal of University of Babylon for Engineering Sciences, 2023)
The research indicates that the use of bitumen is one of the residues of oil refining, made of plastic with tar, which increases its use of power and at the same time gives good stability to the asphalt concrete at high temperatures, and is used in the coating of parking. The recycling of bitumen leads to a reduction in the cost of oil refineries to produce deeper refining, leading to deterioration of the physical and chemical properties of oil tar, and as a result, lead to a decrease in the quality of oil tar. Today, the expansion of raw materials for road bitumen production can be achieved through the use of by-products, construction waste, bitumen recycling,